Controlled pulmonary drug delivery - Smyth, Hugh D.C.; Hickey, Anthony J.; SpringerLink (Online service). (New York Springer, 2011)
This distinctive text provides a toolbox for pharmaceutical scientists and those involved in product development utilizing pulmonary drug delivery systems. Uniquely focusing on aspects of control, both temporal and spatial, the text collects a broad range of interlinked chapters that provide both theoretical and practical insight.   Controlled Pulmonary Drug Delivery begins by examination of the foundations for pulmonary drug delivery: the macro and microstructure of the airways, lung clearance, airway absorption and transport, aerosol physics, and a historical overview of the field. Unlike other texts, these chapters are written specifically with drug delivery in mind. The science and technology of inhaler devices, technologies, materials, and particles systems are covered. Testing methods and techniques are discussed before regulatory perspectives and performance specifications conclude the text. The twenty two novel chapters in this volume each provide a theoretical and practical set of tools that comprise a comprehensive toolbox.   This volume will be of interest to scientists and engineers developing pulmonary drug delivery systems. The unique themes of controlled release science and technology that run through the book ensure that experienced and newcomers will greatly benefit from this book. As the importance for control over therapeutic performance is better recognized and demanded, this text will be essential for those delivering bioactives to the lung. Dr. Hugh Smyth is Assistant Professor of Pharmaceutics at the University of Texas, Austin. He is a recipient of the Young Investigator in Pharmaceutics and Pharmaceutical Technology Award of the American Association of Pharmaceutical Scientists and has edited a volume on pulmonary drug delivery. Drs. Hickey and Smyth share a research interest in the delivery of drugs to the lungs for the treatment and prevention of a number of diseases. Dr. Anthony Hickey is Professor of Molecular Pharmaceutics and Biomedical Engineering at the University of North Carolina at Chapel Hill. He is a fellow of the Institute of Biology, American Association of Pharmaceutical Scientists and the American Association for the Advancement of Science. He has published several edited and authored volumes in the fields of pharmaceutical aerosols, process engineering and particulate science.
Macro And Micro Structure Of The Airways For Drug Delivery -- Pulmonary Drug Metabolism, Clearance, And Absorption -- Pulmonary Drug Delivery: An Historical Overview -- The Physics of Aerosol Droplet and Particle Generation from Inhalers -- Overcoming Lung Clearance Mechanisms For Controlled Release Drug Delivery -- Targeted Drug Delivery Through The Respiratory System: Molecular Control On Lung Absorption And Disposition -- Controlled Transport For Pulmonary Drug Delivery -- Science And Technology Of Metered-Dose Inhalers -- Science And Technology Of Dry Powder Inhalers -- Science And Technology Of Nebulizers And Liquid Based Aerosol Generators -- Excipients Utilized For Modifying Pulmonary Drug Release -- Polymers For Pulmonary Drug Delivery -- Particle Engineering Technologies For Pulmonary Drug Delivery -- Liposomes For Pulmonary Drug Delivery -- Nanoparticles For Pulmonary Delivery -- Pulmonary Delivery Of Plasmid DNA For Disease Prevention And Therapy -- In Vitro Performance Testing For Pulmonary Drug Delivery -- In Vitro Cell Culture Models For Evaluating Controlled Release Pulmonary Drug Delivery -- In Vivo Animal Models For Controlled Release Pulmonary Drug Delivery -- Imaging Pulmonary Drug Delivery -- Development And Approval Of Inhaled Respiratory Drugs: A US Regulatory Science Perspective -- Developing Performance Specifications For Pulmonary Products.
Electronic reproduction.
Keywords: Aerosol therapy; Drug delivery systems; Administration, Inhalation; Aerosols -- Therapeutic use; Drug delivery systems; Lung -- Physiology; Lung diseases -- Drug therapy; Pharmaceutical preparations -- Administration & dosage; Electronic books